Impaired touch sensation on hairy skin in HCN3-deficient mice - Metzner, Katharina; Hussein-Zahovic, Tamara; Behery, Yomna; Fenske, Stefanie; Biel, Martin; Schmidtko, Achim (Frontiers in Neuroscience, 2026)
The hyperpolarization-activated cyclic nucleotide-gated (HCN) channel HCN3 is expressed in sensory dorsal root ganglia (DRG) neurons, but its contribution to somatosensory processing remains poorly understood. Here, using RNA in situ hybridization, we found that Hcn3 is widely expressed in various populations of DRG neurons. Analysis of HCN3-deficient mice in a series of behavioral tests for somatosensory function revealed that HCN3 deletion led to profound impairments in mechanical sensation on hairy skin. However, the mechanical sensation on glabrous skin and responses to noxious heat and cold stimuli were not affected in the absence of HCN3. Electrophysiological recordings revealed that deletion of HCN3 reduced the HCN current (Ih) density and affected the action potential kinetics in thoracic (Th9–Th10) DRG neurons, which innervate hairy skin. However, electrophysiological parameters were unaltered in lumbar (L4–L5) DRG neurons. These findings suggest that HCN3 channels are specific regulators of low-threshold mechanoreceptors that innervate hairy skin.